The Production of Green Diesel Rich Pentadecane (C15) from Catalytic Hydrodeoxygenation of Waste Cooking Oil using Ni/Al2O3-ZrO2 and Ni/SiO2-ZrO2 - Arda Rista Lestari; Eka Novitasari; Masruri Masruri; Siti Mariyah Ulfa; Momodou Salieu Sowe (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Hydrodeoxygenation (HDO) is applied in fuel processing technology to convert bio-oils to green diesel with metal-based catalysts. The major challenges to this process are feedstock, catalyst preparation, and the production of oxygen-free diesel fuel. In this study, we aimed to synthesize Ni catalysts supported on silica-zirconia and alumina-zirconia binary oxides and evaluated their catalytic activity for waste cooking oil (WCO) hydrodeoxygenation to green diesel. Ni/Al2O3-ZrO2 and Ni/SiO2-ZrO2 were synthesized by wet-impregnation and hydrodeoxygenation of WCO was done using a modified batch reactor. The catalysts were characterized using X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy - energy dispersive X-ray spectroscopy (SEM-EDS), and N2 isotherm adsorption-desorption analysis. Gas chromatography - mass spectrometry (GC-MS) analysis showed the formation of hydrocarbon framework n-C15 generated from the use of Ni/Al2O3-ZrO2 with the selectivity of 68.97% after a 2 h reaction. Prolonged reaction into 4 h, decreased the selectivity to 58.69%. Ni/SiO2-ZrO2 catalyst at 2 h showed selectivity of 55.39% to n-C15. Conversely, it was observed that the reaction for 4 h increased selectivity to 65.13%. Overall, Ni/Al2O3-ZrO2 and Ni/SiO2-ZrO2 catalysts produced oxygen-free green diesel range (n-C14-C18) enriched with n-C15 hydrocarbon. Reaction time influenced the selectivity to n-C15 hydrocarbon. Both catalysts showed promising hydrodeoxygenation activity via the hydrodecarboxylation pathway. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).